Method for regulating morphology of in-situ SiC whiskers in SiCf / SiC composite material based on SLS technology
By using SLS technology and steps such as impregnation, crosslinking and curing in SiCf/SiC composites to regulate the in-situ SiC whisker morphology, the problems of high toughness and strength control of composite materials in the prior art are solved, and the controllable and personalized design of performance is achieved.
Patent Information
- Application Number
- CN202411762012.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-04
AI Technical Summary
The prior art cannot use the combination of toughening phase and additive technology to achieve high toughness, or strength and toughness regulation of composite materials.
Using a method based on SLS technology, the composite powder is constructed by adding binder, catalyst and polycarbosilane powder to the carrier powder to realize the regulation of the in-situ SiC whisker morphology in the SiCf/SiC composite material, including impregnation, cross-linking and curing and cracking.
It realizes high toughness and strength control of composite materials, has the characteristics of near-net molding, not affected by the complexity of parts and personalized design, and is suitable for large-scale production.
Smart Images

Figure CN119551999A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of additive manufacturing of ceramic-based composite materials. Background Art
[0002] Silicon carbide-based ceramics have many advantages such as low density, high strength, high temperature resistance and good wear resistance, and are widely used in aviation, aerospace, optics, energy and other fields. However, with the continuous development of science and technology, the traditional silicon carbide ceramic manufacturing method has gradually exposed some problems, such as the difficulty in manufacturing complex space parts, high cost of small batch production, and difficulty in secondary processing. The inherent brittleness of silicon carbide ceramics has further restricted its development. In the traditional method, adding a second phase (particles, whiskers, fibers) material as a toughening phase has become a relatively effective method to increase the toughness of ceramic-based composite materials. At present, for SiC f Most of the molding methods of SiC composite materials are presented through three-dimensional weaving, which requires the help of molds to form, and has the characteristics of long production cycle time and high cost. After the emergence of additive manufacturing technology, it provides a solution for the molding of silicon carbide-based ceramic composites. In particular, additive manufacturing technology has the characteristics of near-net molding, unaffected by the complexity of part space and personalized design, and is favored by many researchers. How to combine the toughening phase with additive technology to increase the toughness of the composite material or prepare a composite material with the required strength, toughness and other indicators, and finally achieve performance regulation is particularly important. However, the existing technology cannot use the combination of toughening phase and additive technology to achieve high toughness of composite materials, or strength and toughness regulation. Summary of the invention
[0003] The present invention aims to solve the problem that the existing technology cannot achieve high toughness of composite materials or strength and toughness regulation by combining toughening phase with additive technology, and thus provide a method for regulating SiC based on SLS technology. f Method for in situ SiC whisker morphology in SiC / SiC composites.
[0004] A method for regulating SiC based on SLS technology f The method for in-situ SiC whisker morphology in a SiC / SiC composite material is carried out in the following steps:
[0005] 1. Preparation of original powder:
[0006] Mixing SiC powder, polycarbosilane, a catalyst and a binder to obtain a mixed powder;
[0007] The catalyst is one or a mixture of two of nano iron powder, nano alumina powder and nano ferric nitrate powder; the particle size of the catalyst is 50nm to 200nm;
[0008] 2. Preparation of SiC ceramic matrix composite material blank:
[0009] Under the conditions of each layer thickness of 0.06 mm to 0.20 mm, preheating temperature of 35° C. to 75° C., printing profile speed of 1400 mm / s to 3000 mm / s, printing profile power of 6 W to 20 W, filling speed of 2000 mm / s to 3700 mm / s, filling power of 8 W to 18 W, and beam spot spacing of 0.1 mm to 0.16 mm during filling, SLS printing was performed using the mixed powder to obtain a SiC ceramic-based composite blank;
[0010] 3. Sintering:
[0011] In an Ar environment, the SiC ceramic matrix composite material blank is heated to 1400°C to 1700°C, then kept at 1400°C to 1700°C for 2h to 8h in an Ar environment, and finally cooled to obtain a skeleton material containing SiC whiskers;
[0012] 4. Impregnation:
[0013] The framework material containing SiC whiskers is placed in a precursor solution, firstly evacuated, then pressurized and maintained, and then taken out after exhausting to obtain the impregnated framework material containing SiC whiskers;
[0014] The precursor solution is prepared from polycarbosilane, divinylbenzene and tetrahydrofuran at room temperature, normal pressure and air atmosphere;
[0015] 5. Cross-linking and curing:
[0016] The impregnated skeleton material containing SiC whiskers is heated to 320° C. to 350° C., and then the impregnated skeleton material containing SiC whiskers is cross-linked and cured for 4 h to 8 h at a temperature of 320° C. to 350° C., and finally the temperature is lowered to obtain a cross-linked and cured skeleton material containing SiC whiskers;
[0017] 6. Cracking:
[0018] In N 2 Under ambient conditions, the cross-linked and cured SiC whisker-containing skeleton material is heated to 1000°C to 1300°C, and then heated under N 2 Under the condition of an environment and a temperature of 1000° C. to 1300° C., the material is kept warm for 20 to 40 minutes, then cooled to 100 to 150° C., and finally cooled to room temperature with water in the furnace to obtain a skeleton material containing SiC whiskers after cracking;
[0019] 7. Cycle processing:
[0020] The cracked SiC whisker-containing skeleton material is repeated multiple times according to steps 4 to 6 to complete the SLS technology-based regulation of SiC fMethod for in situ SiC whisker morphology in SiC / SiC composites.
[0021] The beneficial effects of the present invention are:
[0022] 1. The present invention uses SLS technology as a molding method, and constructs a composite powder by adding a binder, a catalyst and polycarbosilane powder to a powder carrier. With the help of the molding characteristics of SLS technology, near-net molding of parts can be achieved, which is not affected by the complexity of the parts and has the characteristics of personalized customized production.
[0023] Second, the precursor solution of the present invention is prepared at room temperature, normal pressure and air atmosphere, which is simple and convenient, and the function of the solution is only to increase the density of the composite material without introducing other components;
[0024] 3. The pyrolysis temperature of the present invention is low, energy saving, simple process, strong operability, and suitable for large-scale production;
[0025] Fourth, the present invention uses different catalysts to promote the regulation of SiC whisker morphology, and adopts an impregnation cracking method to increase the density of the composite material. Its mechanical properties are controllable, and the impregnation cracking cycle can be selected as needed. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The SiC whisker in-situ grown in Example 1 is f Morphology of SiC whiskers in / SiC composites;
[0027] Figure 2 The SiC whisker in-situ grown in Example 2 is f Morphology of SiC whiskers in / SiC composites;
[0028] Figure 3 The SiC whiskers grown in situ prepared in Example 3 f Morphology of SiC whiskers in / SiC composites;
[0029] Figure 4 The SiC whiskers grown in situ prepared in Example 4 f Morphology of SiC whiskers in / SiC composites;
[0030] Figure 5 The SiC whiskers grown in situ prepared in Example 5 f Morphology of SiC whiskers in / SiC composites;
[0031] Figure 6 The SiC whiskers grown in situ prepared in Example 6 f Morphology of SiC whiskers in / SiC composites. DETAILED DESCRIPTION
[0032] Specific implementation method 1: This implementation method is a method for regulating SiC based on SLS technology f The method for in-situ SiC whisker morphology in a SiC / SiC composite material is carried out in the following steps:
[0033] 1. Preparation of original powder:
[0034] Mixing SiC powder, polycarbosilane, a catalyst and a binder to obtain a mixed powder;
[0035] The catalyst is one or a mixture of two of nano iron powder, nano alumina powder and nano ferric nitrate powder; the particle size of the catalyst is 50nm to 200nm;
[0036] 2. Preparation of SiC ceramic matrix composite material blank:
[0037] Under the conditions of each layer thickness of 0.06 mm to 0.20 mm, preheating temperature of 35° C. to 75° C., printing profile speed of 1400 mm / s to 3000 mm / s, printing profile power of 6 W to 20 W, filling speed of 2000 mm / s to 3700 mm / s, filling power of 8 W to 18 W, and beam spot spacing of 0.1 mm to 0.16 mm during filling, SLS printing was performed using the mixed powder to obtain a SiC ceramic-based composite blank;
[0038] 3. Sintering:
[0039] In an Ar environment, the SiC ceramic matrix composite material blank is heated to 1400°C to 1700°C, then kept at 1400°C to 1700°C for 2h to 8h in an Ar environment, and finally cooled to obtain a skeleton material containing SiC whiskers;
[0040] 4. Impregnation:
[0041] The framework material containing SiC whiskers is placed in a precursor solution, firstly evacuated, then pressurized and maintained, and then taken out after exhausting to obtain the impregnated framework material containing SiC whiskers;
[0042] The precursor solution is prepared from polycarbosilane, divinylbenzene and tetrahydrofuran at room temperature, normal pressure and air atmosphere;
[0043] 5. Cross-linking and curing:
[0044] The impregnated skeleton material containing SiC whiskers is heated to 320° C. to 350° C., and then the impregnated skeleton material containing SiC whiskers is cross-linked and cured for 4 h to 8 h at a temperature of 320° C. to 350° C., and finally the temperature is lowered to obtain a cross-linked and cured skeleton material containing SiC whiskers;
[0045] 6. Cracking:
[0046] In N 2 Under ambient conditions, the cross-linked and cured SiC whisker-containing skeleton material is heated to 1000°C to 1300°C, and then heated under N 2 Under the condition of an environment and a temperature of 1000° C. to 1300° C., the material is kept warm for 20 to 40 minutes, then cooled to 100 to 150° C., and finally cooled to room temperature with water in the furnace to obtain a skeleton material containing SiC whiskers after cracking;
[0047] 7. Cycle processing:
[0048] The cracked SiC whisker-containing skeleton material is repeated multiple times according to steps 4 to 6 to complete the SLS technology-based regulation of SiC f Method for in situ SiC whisker morphology in SiC / SiC composites.
[0049] In this specific implementation method, the required model is drawn by three-dimensional modeling software and exported to .STL format, and the exported .STL format is imported into the SLS printer, and the thickness of each layer is set to 0.06mm~0.20mm, the preheating temperature is 35℃~75℃, the printing profile speed is 1400mm / s~3000mm / s, the printing profile power is 6W~20W, the filling speed is 2000mm / s~3700mm / s, the filling power is 8W~18W, and the beam spot spacing during filling is 0.1mm~0.16mm to complete the layered slicing processing of the model; then the mixed powder is spread all over the SLS printer workbench and the powder feeding cylinders on both sides, the SLS printer safety door is closed, the SLS printer is preheated, and when the set temperature is reached, printing layer by layer is started according to the set parameters. After the printing is completed, after the powder is cooled, the SLS printing safety door is opened, and the parts are taken out and the excess powder is cleaned to obtain the SiC ceramic-based composite material blank.
[0050] This specific embodiment provides a method for regulating SiC based on SLS technology f The method of in-situ SiC whisker morphology in SiC / SiC composites is used to realize additive manufacturing methods and composite SiC whiskers with different morphologies to prepare ceramic-based composites with controllable performance, which provides a method for personalized preparation of ceramic-based composites and performance regulation, which is of great significance to expanding the application of ceramic-based composites.
[0051] The beneficial effects of this embodiment are:
[0052] 1. This embodiment uses SLS technology as the molding method. A composite powder is constructed by adding a binder, a catalyst and polycarbosilane powder to a powder carrier. With the molding characteristics of SLS technology, near-net molding of parts can be achieved, which is not affected by the complexity of the parts and has the characteristics of personalized customized production.
[0053] Second, the precursor solution of this embodiment is prepared at room temperature, normal pressure and air atmosphere, which is simple and convenient, and the function of the solution is only to increase the density of the composite material without introducing other components;
[0054] 3. The cracking temperature of this embodiment is low, energy saving, simple process, strong operability, and suitable for large-scale production;
[0055] Fourth, this embodiment uses different catalysts to promote the regulation of SiC whisker morphology, and uses an impregnation cracking method to increase the density of the composite material. Its mechanical properties are controllable, and the impregnation cracking cycle can be selected as needed.
[0056] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that: the mass ratio of SiC powder to polycarbosilane in step 1 is 1:(0.1-0.2); the mass ratio of SiC powder to catalyst in step 1 is 1:(0.06-0.08); the mass ratio of SiC powder to binder in step 1 is 1:(0.06-0.08); the particle size of SiC powder in step 1 is 60 μm-80 μm. Others are the same as specific embodiment 1.
[0057] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that: in step 1, SiC powder, polycarbosilane, catalyst and binder are mixed for 24h to 48h at a rotation speed of 8r / min to 15r / min. The rest is the same as specific implementation method 1 or 2.
[0058] Specific implementation method 4: This implementation method is different from specific implementation methods 1 to 3 in that the adhesive in step 1 is epoxy resin. The rest is the same as specific implementation methods 1 to 3.
[0059] Specific implementation method 5: This implementation method is different from the specific implementation methods 1 to 4 in that: in step 3, the temperature is raised from room temperature to 150°C to 200°C at a heating rate of 3°C / min to 8°C / min, then raised to 1000°C to 1200°C at a heating rate of 5°C / min to 10°C / min, and finally raised to 1400°C to 1700°C at a heating rate of 3°C / min to 8°C / min; the cooling described in step 3 is to first cool the temperature from 1400°C to 1700°C to 1000°C to 1200°C at a cooling rate of 3°C / min to 8°C / min, then cool it to 150°C to 200°C at a cooling rate of 5°C / min to 10°C / min, and finally cool it to room temperature at a cooling rate of 3°C / min to 8°C / min; the Ar flow rate in the Ar environment described in step 3 is 3sccm to 5sccm. Others are the same as the specific implementation methods 1 to 4.
[0060] The purpose of this specific embodiment is to volatilize the organic solution in the precursor solution, increase the molecular weight of polycarbosilane, and improve the ceramic conversion yield.
[0061] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that: the concentration of polycarbosilane in the precursor solution described in step 4 is 120 g / 100 mL to 140 g / 100 mL; the mass ratio of polycarbosilane to divinylbenzene in the precursor solution described in step 4 is 1:(0.6 to 0.8). Others are the same as specific embodiments 1 to 5.
[0062] Specific embodiment 7: This embodiment differs from Specific embodiments 1 to 6 in that: in step 4, the vacuum is evacuated to -0.2MPa to 0MPa, and then the pressure is maintained at 2MPa to 3MPa for 30min to 60min. The rest is the same as Specific embodiments 1 to 6.
[0063] Specific embodiment eight: This embodiment differs from one of specific embodiments one to seven in that: in step five, the temperature is raised from room temperature to 100°C to 120°C at a heating rate of 3°C / min to 5°C / min, then raised to 200°C to 250°C at a heating rate of 5°C / min to 10°C / min, and finally raised to 320°C to 350°C at a heating rate of 3°C / min to 8°C / min; the cooling described in step five is firstly to cool the temperature from 320°C to 350°C to 200°C to 250°C at a cooling rate of 3°C / min to 8°C / min, then to 100°C to 120°C at a cooling rate of 5°C / min to 10°C / min, and finally to room temperature at a cooling rate of 3°C / min to 5°C / min. The rest is the same as specific embodiments one to seven.
[0064] Specific embodiment 9: This embodiment is different from specific embodiments 1 to 8 in that: in step 6, the temperature is raised from room temperature to 100°C to 150°C at a heating rate of 3°C / min to 8°C / min, then the temperature is raised to 800°C to 1000°C at a heating rate of 5°C / min to 10°C / min, and finally the temperature is raised to 1100°C to 1300°C at a heating rate of 3°C / min to 8°C / min; in step 6, the temperature is first lowered from 1100°C to 1300°C to 800°C to 1000°C at a cooling rate of 3°C / min to 8°C / min, then the temperature is lowered to 100°C to 150°C at a cooling rate of 5°C / min to 10°C / min, and finally the furnace is water-cooled to room temperature. The rest is the same as specific embodiments 1 to 8.
[0065] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that in step 7, the cracked SiC whisker-containing skeleton material is repeatedly subjected to steps 4 to 6 for multiple times until the required toughness and strength are achieved, or until the weight gain is ≤1%. Other aspects are the same as specific embodiments 1 to 9.
[0066] The following examples are used to verify the beneficial effects of the present invention:
[0067] Embodiment 1:
[0068] A method for regulating SiC based on SLS technology f The method for in-situ SiC whisker morphology in a SiC / SiC composite material is carried out in the following steps:
[0069] 1. Preparation of original powder:
[0070] Mixing SiC powder, polycarbosilane, a catalyst and a binder to obtain a mixed powder;
[0071] The catalyst is nano iron powder; the average particle size of the catalyst is 100nm;
[0072] 2. Preparation of SiC ceramic matrix composite material blank:
[0073] Under the conditions of each layer thickness of 0.08 mm, preheating temperature of 60 ° C, printing profile speed of 2000 mm / s, printing profile power of 12 W, filling speed of 2200 mm / s, filling power of 14 W and beam spot spacing of 0.12 mm during filling, SLS printing was performed using the mixed powder to obtain a SiC ceramic matrix composite blank;
[0074] 3. Sintering:
[0075] In an Ar environment, the SiC ceramic matrix composite material blank is heated to 1600°C, then kept at 1600°C for 6 hours in an Ar environment, and finally cooled to obtain a skeleton material containing SiC whiskers.
[0076] 4. Impregnation:
[0077] The framework material containing SiC whiskers is placed in a precursor solution, firstly evacuated, then pressurized and maintained, and then taken out after exhausting to obtain the impregnated framework material containing SiC whiskers;
[0078] The precursor solution is prepared from polycarbosilane, divinylbenzene and tetrahydrofuran at room temperature, normal pressure and air atmosphere;
[0079] 5. Cross-linking and curing:
[0080] The impregnated skeleton material containing SiC whiskers is heated to 350° C., and then the impregnated skeleton material containing SiC whiskers is cross-linked and cured for 6 hours at 350° C., and finally the temperature is lowered to obtain a cross-linked and cured skeleton material containing SiC whiskers;
[0081] 6. Cracking:
[0082] In N 2 Under ambient conditions, the cross-linked and cured SiC whisker-containing skeleton material was heated to 1200°C and then heated to 400°C under N 2 Under the condition of an environment and a temperature of 1200°C, the material is kept warm for 30 minutes, then cooled to 150°C, and finally cooled to room temperature with water in the furnace to obtain a framework material containing SiC whiskers after cracking;
[0083] 7. Cycle processing:
[0084] The cracked framework material containing SiC whiskers is repeated multiple times according to steps 4 to 6 to obtain a SiC whisker-grown in-situ SiC f / SiC composite materials.
[0085] The mass ratio of the SiC powder to polycarbosilane described in step one is 16:2; the mass ratio of the SiC powder to the catalyst described in step one is 16:1; the mass ratio of the SiC powder to the binder described in step one is 16:1; the average particle size of the SiC powder described in step one is 75 μm.
[0086] In step 1, SiC powder, polycarbosilane, catalyst and binder are mixed for 48 hours at a rotation speed of 10 r / min.
[0087] The binder described in step 1 is epoxy resin (E-12 from Guangzhou Xinxi Metallurgical Chemical Co., Ltd.).
[0088] In step three, the temperature is increased from room temperature to 200°C at a heating rate of 3°C / min, then increased to 1200°C at a heating rate of 10°C / min, and finally increased to 1600°C at a heating rate of 3°C / min; the cooling described in step three is firstly reduced from 1600°C to 1200°C at a cooling rate of 3°C / min, then reduced to 200°C at a cooling rate of 10°C / min, and finally reduced to room temperature at a cooling rate of 3°C / min.
[0089] The Ar flow rate in the Ar environment described in step 3 is 5 sccm.
[0090] The concentration of polycarbosilane in the precursor solution described in step 4 is 133.3 g / 100 mL; the mass ratio of polycarbosilane to divinylbenzene in the precursor solution described in step 4 is 10:8; the preparation process is specifically to first mix polycarbosilane and divinylbenzene in a mass ratio of 10:8 at room temperature, normal pressure and air atmosphere, and then add tetrahydrofuran to completely dissolve the polycarbosilane.
[0091] In step 4, the pressure is evacuated to -0.1 MPa, and then the pressure is maintained at 3 MPa for 45 minutes.
[0092] In step 5, the temperature is increased from room temperature to 120°C at a heating rate of 3°C / min, then increased to 250°C at a heating rate of 7°C / min, and finally increased to 350°C at a heating rate of 3°C / min; the cooling described in step 5 is first cooled from 350°C to 250°C at a cooling rate of 3°C / min, then cooled to 120°C at a cooling rate of 7°C / min, and finally cooled to room temperature at a cooling rate of 3°C / min.
[0093] In step six, the temperature is increased from room temperature to 150°C at a heating rate of 5°C / min, then increased to 1000°C at a heating rate of 10°C / min, and finally increased to 1200°C at a heating rate of 5°C / min; in step six, the temperature is first decreased from 1200°C to 1000°C at a cooling rate of 5°C / min, then decreased to 150°C at a cooling rate of 10°C / min, and finally cooled to room temperature with furnace water.
[0094] In step 7, the cracked SiC whisker-containing skeleton material is repeatedly subjected to steps 4 to 6 for multiple times until the weight gain rate is ≤1%.
[0095] Embodiment 2: This embodiment is different from Embodiment 1 in that the catalyst in step 1 is nano-alumina powder. The rest is the same as Embodiment 1.
[0096] Embodiment 3: This embodiment is different from Embodiment 1 in that the catalyst in step 1 is nano iron nitrate powder. The rest is the same as Embodiment 1.
[0097] Embodiment 4: This embodiment is different from Embodiment 1 in that the catalyst in step 1 is a mixture of nano iron powder and nano alumina powder in a mass ratio of 1:1. The rest is the same as Embodiment 1.
[0098] Embodiment 5: This embodiment is different from Embodiment 1 in that the catalyst in step 1 is a mixture of nano iron powder and nano ferric nitrate powder in a mass ratio of 1:1. The rest is the same as Embodiment 1.
[0099] Embodiment 6: This embodiment is different from Embodiment 1 in that the catalyst in step 1 is a mixture of nano-alumina powder and nano-ferric nitrate powder in a mass ratio of 1:1. The rest is the same as Embodiment 1.
[0100] Figure 1 The SiC whisker in-situ grown in Example 1 is f The morphology of SiC whiskers in the SiC / SiC composite material; it can be seen from the figure that most of the tips of the SiC whiskers are in the shape of a "shuttle", thin at both ends and thick in the middle, and the whiskers at the tip and bottom are thinner. The aspect ratio range is 81.30 to 84.27 after a large amount of data measurement. According to GB / T6569-2006 "Fine Ceramics Bending Strength Test Method" and GB / T23806-2009 "Fine Ceramics Fracture Toughness Test Method Single Edge Precracked Beam (SEPB) Method" standards, the SiC whiskers of the in-situ grown SiC whiskers prepared in Example 1 were tested. f The bending strength and fracture toughness of the / SiC composite material were tested. The bending strength was 217.32MPa and the fracture toughness was 4.83Pa·m at room temperature. 1 / 2 ; Under 1300℃ vacuum environment, the bending strength is 204.28MPa and the fracture toughness is 4.54MPa·m 1 / 2 .
[0101] Figure 2 The SiC whisker in-situ grown in Example 2 is f The morphology of SiC whiskers in the SiC / SiC composite material; As can be seen from the figure, it can be found that the SiC whiskers are "upright" in shape, and most of them exist vertically on the surface of the SiC particles. There is no crossing phenomenon between most whiskers. According to a large amount of data measurement and statistics, the aspect ratio range is 78.23 to 81.84. According to GB / T6569-2006 "Fine Ceramics Bending Strength Test Method" and GB / T23806-2009 "Fine Ceramics Fracture Toughness Test Method Single Edge Precracked Beam (SEPB) Method" standards, the SiC of the in-situ grown SiC whiskers prepared in Example 2 fThe bending strength and fracture toughness of the / SiC composite material were tested. The bending strength was 202.17MPa and the fracture toughness was 4.06MPa·m at room temperature. 1 / 2 ; Under 1300℃ vacuum environment, the bending strength is 189.43MPa and the fracture toughness is 3.79MPa·m 1 / 2 .
[0102] Figure 3 The SiC whiskers grown in situ prepared in Example 3 f The morphology of SiC whiskers in the SiC / SiC composite material; as can be seen from the figure, most of the SiC whiskers are intertwined with each other and are uniform in thickness, but the whisker density is relatively small. According to a large amount of data measurement, the aspect ratio range is 89.52 to 90.16. According to GB / T6569-2006 "Fine Ceramics Bending Strength Test Method" and GB / T23806-2009 "Fine Ceramics Fracture Toughness Test Method Single Edge Precracked Beam (SEPB) Method" standards, the SiC whiskers of in-situ growth prepared in Example 3 were tested. f The bending strength and fracture toughness of the SiC composite material were tested. The bending strength was 228.95 MPa and the fracture toughness was 4.97 MPa·m at room temperature. 1 / 2 ; Under vacuum at 1300℃, the bending strength is 217.51MPa and the fracture toughness is 4.68MPa·m 1 / 2 .
[0103] Figure 4 The SiC whiskers grown in situ prepared in Example 4 f / The morphology of SiC whiskers in SiC composite materials; As can be seen from the figure, most of the SiC whiskers show an interweaving phenomenon, the surface whiskers are coarser than the internal whiskers, and most of the whiskers also have the characteristics of thick ends and thin roots. The internal whiskers are slender and curly, and the whisker density is relatively large. According to a large amount of data measurement and statistics, its aspect ratio range is 93.36~95.18. According to GB / T6569-2006 "Fine Ceramics Bending Strength Test Method" and GB / T23806-2009 "Fine Ceramics Fracture Toughness Test Method Single Edge Pre-cracked Beam (SEPB) Method" standards, the SiC of the in-situ grown SiC whiskers prepared in Example 4 was f The bending strength and fracture toughness of the / SiC composite material were tested. The bending strength was 237.68MPa and the fracture toughness was 6.17MPa·m at room temperature. 1 / 2 ; Under vacuum at 1300℃, the bending strength is 227.46MPa and the fracture toughness is 5.67MPa·m 1 / 2 .
[0104] Figure 5The SiC whiskers grown in situ prepared in Example 5 f The morphology of SiC whiskers in the SiC / SiC composite material; as can be seen from the figure, most of the SiC whiskers are intertwined with each other, with uniform thickness and relatively large whisker density. According to a large amount of data measurement, the aspect ratio range is 97.61 to 99.57. According to GB / T6569-2006 "Fine Ceramics Bending Strength Test Method" and GB / T23806-2009 "Fine Ceramics Fracture Toughness Test Method Single Edge Precracked Beam (SEPB) Method" standards, the SiC whiskers of in-situ growth prepared in Example 5 were tested. f The bending strength and fracture toughness of the / SiC composite material were tested. The bending strength was 245.86MPa and the fracture toughness was 6.73MPa·m at room temperature. 1 / 2 ; Under vacuum at 1300℃, the bending strength is 233.34MPa and the fracture toughness is 6.26MPa·m 1 / 2 .
[0105] Figure 6 The SiC whiskers grown in situ prepared in Example 6 f The morphology of SiC whiskers in the SiC / SiC composite material; as can be seen from the figure, most of the SiC whiskers are intertwined with each other, and the whiskers are mostly thick at the end and thin at the root, and the whisker density is relatively large. According to a large amount of data measurement, the aspect ratio range is 91.62 to 94.37. According to GB / T6569-2006 "Fine Ceramics Bending Strength Test Method" and GB / T23806-2009 "Fine Ceramics Fracture Toughness Test Method Single Edge Precracked Beam (SEPB) Method" standards, the SiC whiskers of in-situ growth prepared in Example 6 were tested. f The bending strength and fracture toughness of the / SiC composite material were tested. The bending strength was 239.73MPa and the fracture toughness was 6.46MPa·m at room temperature. 1 / 2 ; Under vacuum at 1300℃, the bending strength is 226.51MPa and the fracture toughness is 6.15MPa·m 1 / 2 .
Claims
1. A method for regulating SiC based on SLS technology f A method for in-situ SiC whisker morphology in a SiC / SiC composite material, characterized in that It is carried out in the following steps:
1. Preparation of original powder: Mixing SiC powder, polycarbosilane, a catalyst and a binder to obtain a mixed powder; The catalyst is one or a mixture of two of nano iron powder, nano alumina powder and nano ferric nitrate powder; the particle size of the catalyst is 50nm to 200nm; 2. Preparation of SiC ceramic matrix composite material blank: Under the conditions of each layer thickness of 0.06 mm to 0.20 mm, preheating temperature of 35° C. to 75° C., printing profile speed of 1400 mm / s to 3000 mm / s, printing profile power of 6 W to 20 W, filling speed of 2000 mm / s to 3700 mm / s, filling power of 8 W to 18 W, and beam spot spacing of 0.1 mm to 0.16 mm during filling, SLS printing was performed using the mixed powder to obtain a SiC ceramic-based composite blank; 3. Sintering: In an Ar environment, the SiC ceramic matrix composite material blank is heated to 1400°C to 1700°C, then kept at 1400°C to 1700°C for 2h to 8h in an Ar environment, and finally cooled to obtain a skeleton material containing SiC whiskers; 4. Impregnation: The framework material containing SiC whiskers is placed in a precursor solution, firstly evacuated, then pressurized and maintained, and then taken out after exhausting to obtain the impregnated framework material containing SiC whiskers; The precursor solution is prepared from polycarbosilane, divinylbenzene and tetrahydrofuran at room temperature, normal pressure and air atmosphere; 5. Cross-linking and curing: The impregnated skeleton material containing SiC whiskers is heated to 320° C. to 350° C., and then the impregnated skeleton material containing SiC whiskers is cross-linked and cured for 4 h to 8 h at a temperature of 320° C. to 350° C., and finally the temperature is lowered to obtain a cross-linked and cured skeleton material containing SiC whiskers; 6. Cracking: In N2 environment, the cross-linked and cured skeleton material containing SiC whiskers is heated to 1000°C to 1300°C, then kept warm for 20min to 40min in N2 environment and at 1000°C to 1300°C, then cooled to 100°C to 150°C, and finally cooled to room temperature with furnace water to obtain a cracked skeleton material containing SiC whiskers; 7. Cycle processing: The cracked SiC whisker-containing skeleton material is repeated multiple times according to steps 4 to 6 to complete the SLS technology-based regulation of SiC f Method for in situ SiC whisker morphology in SiC / SiC composites.
2. A method for controlling SiC based on SLS technology according to claim 1 f A method for in-situ SiC whisker morphology in a SiC / SiC composite material, characterized in that The mass ratio of the SiC powder described in step one to polycarbosilane is 1:(0.1-0.2); the mass ratio of the SiC powder described in step one to the catalyst is 1:(0.06-0.08); the mass ratio of the SiC powder described in step one to the binder is 1:(0.06-0.08); the particle size of the SiC powder described in step one is 60μm-80μm.
3. A method for controlling SiC based on SLS technology according to claim 1 f A method for in-situ SiC whisker morphology in a SiC / SiC composite material, characterized in that In step 1, SiC powder, polycarbosilane, catalyst and binder are mixed for 24h to 48h at a rotation speed of 8r / min to 15r / min.
4. A method for controlling SiC based on SLS technology according to claim 1 f A method for in-situ SiC whisker morphology in a SiC / SiC composite material, characterized in that The adhesive described in step 1 is epoxy resin.
5. The method according to claim 1 for controlling SiC based on SLS technology f A method for in-situ SiC whisker morphology in a SiC / SiC composite material, characterized in that In step 3, the temperature is increased from room temperature to 150°C to 200°C at a heating rate of 3°C / min to 8°C / min, then increased to 1000°C to 1200°C at a heating rate of 5°C / min to 10°C / min, and finally increased to 1400°C to 1700°C at a heating rate of 3°C / min to 8°C / min; the cooling described in step 3 is first cooled from 1400°C to 1700°C to 1000°C to 1200°C at a cooling rate of 3°C / min to 8°C / min, then cooled to 150°C to 200°C at a cooling rate of 5°C / min to 10°C / min, and finally cooled to room temperature at a cooling rate of 3°C / min to 8°C / min; the Ar flow rate in the Ar environment described in step 3 is 3sccm to 5sccm.
6. A method for controlling SiC based on SLS technology according to claim 1 f A method for in-situ SiC whisker morphology in a SiC / SiC composite material, characterized in that The concentration of polycarbosilane in the precursor solution described in step 4 is 120 g / 100 mL to 140 g / 100 mL; the mass ratio of polycarbosilane to divinylbenzene in the precursor solution described in step 4 is 1:(0.6 to 0.8).
7. The method for controlling SiC based on SLS technology according to claim 1 f A method for in-situ SiC whisker morphology in a SiC / SiC composite material, characterized in that In step 4, the pressure is evacuated to -0.2 MPa to 0 MPa, and then the pressure is maintained at 2 MPa to 3 MPa for 30 min to 60 min.
8. The method according to claim 1 for controlling SiC based on SLS technology f A method for in-situ SiC whisker morphology in a SiC / SiC composite material, characterized in that In step 5, the temperature is raised from room temperature to 100°C to 120°C at a heating rate of 3°C / min to 5°C / min, then raised to 200°C to 250°C at a heating rate of 5°C / min to 10°C / min, and finally raised to 320°C to 350°C at a heating rate of 3°C / min to 8°C / min; the cooling described in step 5 is first cooled from 320°C to 350°C to 200°C to 250°C at a cooling rate of 3°C / min to 8°C / min, then cooled to 100°C to 120°C at a cooling rate of 5°C / min to 10°C / min, and finally cooled to room temperature at a cooling rate of 3°C / min to 5°C / min.
9. The method according to claim 1 for controlling SiC based on SLS technology f A method for in-situ SiC whisker morphology in a SiC / SiC composite material, characterized in that In step six, the temperature is raised from room temperature to 100°C to 150°C at a heating rate of 3°C / min to 8°C / min, then raised to 800°C to 1000°C at a heating rate of 5°C / min to 10°C / min, and finally raised to 1100°C to 1300°C at a heating rate of 3°C / min to 8°C / min; in step six, the temperature is first lowered from 1100°C to 1300°C to 800°C to 1000°C at a cooling rate of 3°C / min to 8°C / min, then lowered to 100°C to 150°C at a cooling rate of 5°C / min to 10°C / min, and finally cooled to room temperature with furnace water.
10. The method for controlling SiC based on SLS technology according to claim 1 f A method for in-situ SiC whisker morphology in a SiC / SiC composite material, characterized in that In step 7, the cracked SiC whisker-containing skeleton material is repeatedly processed according to steps 4 to 6 for multiple times until the required toughness and strength are achieved, or until the weight gain rate is ≤1%.